1989
DOI: 10.1007/bf00397586
|View full text |Cite
|
Sign up to set email alerts
|

Non-hydraulic signals from maize roots in drying soil: inhibition of leaf elongation but not stomatal conductance

Abstract: Conditions of soil drying and plant growth that lead to non-hydraulic inhibition of leaf elongation and stomatal conductance in maize (Zea mays L.) were investigated using plants grown with their root systems divided between two containers. The soil in one container was allowed to dry while the other container was kept well-watered. Soil drying resulted in a maximum 35% inhibition of leaf elongation rate which occurred during the light hours, with no measurable decline in leaf water potential (ψw). Leaf area w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0
3

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(113 citation statements)
references
References 16 publications
7
103
0
3
Order By: Relevance
“…This is indeed a limitation of our data. However, our results may be supported by the findings of Saab & Sharp (1989) with corn, and Blum et al (1991) with wheat. In split-root experiments, they observed that the exposure of a relatively small part of a plant root system to a dry soil significantly reduced plant growth.…”
Section: Resultssupporting
confidence: 85%
“…This is indeed a limitation of our data. However, our results may be supported by the findings of Saab & Sharp (1989) with corn, and Blum et al (1991) with wheat. In split-root experiments, they observed that the exposure of a relatively small part of a plant root system to a dry soil significantly reduced plant growth.…”
Section: Resultssupporting
confidence: 85%
“…Michelena & Boyer 1982). Furthermore, shoot growth can be so sensitive to soil drying that substantial inhibition can occur before the development of decreased water potentials in the aerial plant parts (Saab & Sharp 1989;Gowing, Davies & Jones 1990), and such observations have led to much interest in the involvement of non-hydraulic regulatory signals from the roots (Davies & Zhang 1991;Davies et al . 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Two approaches were used in the studies that changed the view on how plants sense a drying soil. One approach consisted of splitting roots into two containers and applying a low soil water treatment in one of the containers (BLACKMAN & DAVIES, 1985;TERMAAT et al, 1985;ZHANG et al, 1987;SAAD & SHARP, 1989). In this approach, part of the root system was kept in dry soil and part in wet soil, but plants were still able to take up sufficient water to maintain leaf water potential as high as in the control plants, which had their entire root system in wet soil.…”
Section: The Possible Mechanisms By Which Plants Sense a Drying Soilmentioning
confidence: 99%
“…BLACKMAN & DAVIES, 1985;TERMAAT et al, 1985;GOLLAN et al, 1986;SAAD & SHARP, 1989), and the experiments supporting a stomatal response to leaves water status were in woody and semi-woody species (e.g. SALIENDRA et al, 1995;FUCHS & LIVINGSTON, 1996;COMSTOCK & MENCUCCINI, 1998).…”
Section: Ciência Rural V34 N2 Mar-abr 2004mentioning
confidence: 99%